2004
DOI: 10.1111/j.1365-2141.2004.05108.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic of regulatory CD25high and activated CD134+ (OX40) T lymphocytes during acute and chronic graft‐versus‐host disease after allogeneic bone marrow transplantation

Abstract: ex vivo expansion protocols, OX40 blocking might be crucial to optimize the use of Treg to prevent GVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 28 publications
(32 reference statements)
3
39
0
2
Order By: Relevance
“…Other researchers have investigated the relationship between the frequency of CD3 þ CD4 þ CD25 high Tregs in peripheral blood and the incidence of GVHD after alloHSCT, but results have been inconsistent, possibly due to differences in the definition of CD25 high . [6][7][8] The intracellular protein derived from the FOXP3 gene has since been detected using flow cytometry, and is recognized as both a master regulatory gene and a unique marker for these Tregs. 9,10 This procedure enables the specific measurement of Tregs, and distinguishes them from activated conventional CD4 þ CD25 þ T-cells.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have investigated the relationship between the frequency of CD3 þ CD4 þ CD25 high Tregs in peripheral blood and the incidence of GVHD after alloHSCT, but results have been inconsistent, possibly due to differences in the definition of CD25 high . [6][7][8] The intracellular protein derived from the FOXP3 gene has since been detected using flow cytometry, and is recognized as both a master regulatory gene and a unique marker for these Tregs. 9,10 This procedure enables the specific measurement of Tregs, and distinguishes them from activated conventional CD4 þ CD25 þ T-cells.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies a deficit of these cells was found in GvHD, [25][26][27] in other studies no difference was recorded between patients with or without disease 28,29 and yet other studies indicated that regulatory T cells may be increased in patients with chronic GvHD. 30,31 The redundancy of mechanisms potentially involved in GvHD hinders development of new diagnostic methods and therapies. The type of immune response likely reflects the immune status of the patient and donor, the transplant preparative regimen and underlying diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Sanchez et al 74 conducted similar study on 35 consecutive patients who underwent alloHCT. They found a small, but not statistically significant, increase in the absolute number of CD4 þ CD25 high Tregs in patients with cGVHD compared to patients without the disease.…”
Section: Tregs In Human Gvhdmentioning
confidence: 92%
“…Conflicting data have been reported with regards to the role of Tregs in the development of cGVHD in humans (Table 3). [73][74][75][76][77] The first study was performed by Clark et al 73 in which they defined Treg as CD4 þ CD25 high and used flow cytometry to measure the size of the Treg pool in peripheral blood of 40 patients who survived more than 100 days after alloHCT. The authors reported that patients with cGVHD had a significant increased Tregs, expressed both as a percentage of CD4 þ T cells or as absolute counts, compared to patients without cGVHD.…”
Section: Tregs In Human Gvhdmentioning
confidence: 99%